A new genus and two new species of planthopper in the tribe Cenchreini (Hemiptera: Auchenorrhyncha: Derbidae) from lowland tropical rainforest in Costa Rica - Bahder, Brian W.; Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Helmick, Ericka E.; Bartlett, Charles R. (Zootaxa, 2021)
Recent survey work for planthoppers at La Selva Biological Station in Costa Rica found two new species allied with Cenchrea Westwood. The cytochrome c oxidase subunit I (COI) and 18S were sequenced for the new taxa and used these data to assess the genus-level standing of the new taxa. The new taxa do not cluster with Cenchrea dorsalis Westwood, the type species of Cenchrea. A new genus Tico gen. n. described for the reception of new species described as Tico emmettcarri sp. n. (the type species) and Tico pseudosororius sp. n. Cenchrea sororia Fennah is moved to Tico gen. n., to form the new combination Tico sororius (Fennah). Tico gen. n. is compared with allied genera, and review genus-level diagnostic features and the species composition of Cenchrea, which appears to be compositionally heterogenous, but additional data is needed to evaluate genus-level placement of most species.